Xác định Magnitude động đất địa phương ML dựa trên số liệu trạm động đất Hà Nội và Điện Biên - Sơn, Lê Tử (Vietnam Journal of Earth Sciences, 2008)
Using records from Dien Bien and Hanoi seismological stations for determining the local magnitude